Compressive and thermal properties of foamed concrete at high temperature. Issue 6 (2nd November 2022) - Xi, Huifeng; Yao, Yiming; Sun, Yuanfeng; Mobasher, Barzin; Liu, Yiping; Ma, Hongwei
Abstract : Foamed concrete is an attractive material for structural use and insulation of buildings, which can replace flammable organic insulating materials on the market. This study investigated the compressive and thermal properties of the plain, fly ash and expanded polystyrene (EPS) foamed concrete ranging widely in density from 180 to 1800 kg/m 3 . Furthermore, the compressive strength of the plain foamed concrete was analyzed at four density levels of 180, 325, 450, and 595 kg/m 3 and at four temperatures of room temperature, 300, 600, and 900 °C to quantify its fire resistance. The compressive strength of the foamed concrete dramatically declined, and it suffered severe damage when the temperature was higher than 300 °C. A constitutive stress–strain model incorporating the compressive strength–density relationship and the temperature effects was also proposed for the plain foamed concrete. The findings may provide new perspectives on the existing design codes for energy efficiency and fire protection.